Evaluation of outcomes associated with trial of labor after cesarean delivery after a change in clinical practice guidelines in an academic hospital. (2nd September 2017) - Bellows, Patricia; Shah, Utsavi; Hawley, Lauren; Drexler, Kathleen; Gandhi, Manisha; Sangi-Haghpeykar, Haleh; Davidson, Christina
Abstract: Objective : To evaluate maternal–neonatal morbidity for women undergoing trial of labor after cesarean (TOLAC) following clinical practice changes based upon ACOG's 2010 VBAC guideline. Study design : Four-year retrospective cohort analysis around implementation of a hospital guideline in women undergoing TOLAC with a live, cephalic, singleton without lethal anomaly ≥24 weeks and ≥1 prior cesarean. Maternal–neonatal outcomes pre- and post-guideline implementation were compared. Primary outcome was composite maternal morbidity (uterine rupture or dehiscence, hysterectomy, transfusion, thromboembolism, operative/delivery injury, chorioamnionitis/endometritis, shoulder dystocia, death). Secondary outcomes included neonatal morbidity. Results : Four hundred and fifty women underwent TOLAC before and 781 after guideline implementation. Post-guideline, there was a significant increase in age, body mass index, labor length, women with >1 cesarean, comorbid condition and induced labor. Composite maternal morbidity was significantly higher after the guideline (13.78% versus 18.82%, p  = 0.02), possibly due to an increased rate of chorioamnionitis/endometritis, which was no longer significant after control for potential confounders in multivariable analysis. There were no differences in neonatal outcomes. Vaginal birth after cesarean (VBAC) success rates were unchanged (78.9% before versus 78.1% after, p  = 0.75), however hospital VBAC rates increased after the guideline (26% versus 33%, p  < 0.0001). Conclusions : Adoption of ACOG's TOLAC practice changes can increase VBAC rates without increasing maternal–neonatal morbidity from TOLAC.